Current and future use of umifenovir in patients with COVID-19 - Yu. Yu. Kiselev; K. A. Zagorodnikova; D. V. Ivashchenko; A. V. Krykov; I. N. Sychev; A. S. Matveev; K. B. Mirzaev; V. A. Otdelenov; V. M. Tsvetov; A. V. Dmitriev; V. V. Poroikov; D. A. Sychev (Izdatelstvo OKI, 2020)
At the time of print, the evidence for using umifenovir in COVID-19 is mainly theoretical. The published clinical trials have contradicting results. The decision to use umifenovir in COVID-19 should be individualized, considering the "experimental" nature of this treatment.